Analisis Perlindungan Konsumen Dari Perusahaan Fintech Ilegal Melalui Pelaksanaan Mekanisme Regulatory Sandbox Sebagai Upaya Akselerasi Usaha Mikro Kecil dan Menengah - Rizky Novianto, Muhammad (Universitas Ekasakti, 2024)
The development of financial technology (fintech) innovation is something that cannot be avoided by various parties. Its rapid development needs to be harmonized with the regulation and protection of business actors and consumers, especially with the rise of illegal fintech. One of OJK's efforts to mitigate this risk is to implement a Regulatory Sandbox mechanism as a fintech trial that will operate later. However, in the Regulatory Sandbox mechanism, there is a weakness in that there is no follow-up assistance mechanism for fintech companies that have been declared not recommended by the OJK. So that the authors in this paper use normative juridical research methods, to study laws and regulations regarding the Regulatory Sandbox and consumer protection, which results in research that it’s necessary to have thhe formulation off an advanced regulatory sandbox assistance mechanism which is then translated into the reassessment stage, the re-assistance stage. , and the recovery stage. Apart from that, the concept of an advanced mechanism also needs to be accommodated in POJK Number 13/POJK.02/2018 along with its technical provisions, namely SEOJK Number 21/SEOJK.02/2019.